2015
DOI: 10.1097/ncc.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Positive Coping, and Quality of Life Among Women Newly Diagnosed With Gynecological Cancers

Abstract: Background Resilience has been linked to psychological adaptation to many challenging life events. Objective The goal was to examine three coping strategies - expressing positive emotions, positive reframing of the cancer experience, and cultivating a sense of peace and meaning in life - as potential mechanisms by which resilience translates to quality of life among women recently diagnosed with gynecological cancer. Method This cross-sectional study utilized baseline data from women diagnosed with gynecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 52 publications
9
45
1
4
Order By: Relevance
“…While both groups experienced common stressors, their difference in their general outlook on work influenced how they saw themselves and their attitudes within the working environment. In one way, their role as a nurse and their disposition toward the challenges they faced at work were similar to those in a previous study by Ablett and Jones () and Manne et al (), who found that a strong sense of meaning and purpose in life and disposition toward challenges influenced participants' growth and development. When faced with challenging situations, highly‐resilient nurses felt they were in control of the situation, while nurses with low resilience did not.…”
Section: Discussionsupporting
confidence: 84%
“…While both groups experienced common stressors, their difference in their general outlook on work influenced how they saw themselves and their attitudes within the working environment. In one way, their role as a nurse and their disposition toward the challenges they faced at work were similar to those in a previous study by Ablett and Jones () and Manne et al (), who found that a strong sense of meaning and purpose in life and disposition toward challenges influenced participants' growth and development. When faced with challenging situations, highly‐resilient nurses felt they were in control of the situation, while nurses with low resilience did not.…”
Section: Discussionsupporting
confidence: 84%
“…The negative relationship between age and resilience was modest (β = −0.108, P = 0.036), suggesting that younger patients reported greater resilience. It is inconsistent with previous reports regarding the association between age and resilience [14, 45]. Rosenberg [14] found age was positively associated with resilience and Manne [45] reported there was no difference in resilience among cancer patients based on age.…”
Section: Discussionmentioning
confidence: 61%
“…It is inconsistent with previous reports regarding the association between age and resilience [14, 45]. Rosenberg [14] found age was positively associated with resilience and Manne [45] reported there was no difference in resilience among cancer patients based on age. There is a paucity of research examining the association between age and resilience among adults with cancer.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Resilience is an important indicator of mental health and plays an important role in the process of mental adaptation [1][2], can negatively predict psychological problems such as subjective stress, anxiety and depression, and positively predict quality of life [3][4][5][6][7]. From the perspective of the formation mechanism, resilience is the adaptation process in which an individual realizes good adaptation through reasonable response in the face of setbacks or stressful events.…”
Section: Introductionmentioning
confidence: 99%